EFFECT OF ECO ENZYME ADDITION ON THE IMPROVEMENT OF WATER QUALITY, REDUCTION OF AMMONIA AND METAL IN DUG WELL WATER - Pangestu Pradana Hardiawanto; Maya Istyadji; Yasmine Khairunnisa (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
This study aims to: (1) Analyze the effect of artificial eco enzyme addition on improving the quality of dug well water based on pH, TDS, TSS, and DO parameters; (2) Analyze the effect of artificial eco enzyme addition on reducing ammonia and metal content in dug well water. The type of research is a laboratory-scale experiment with a quantitative approach to dug well water samples treated using a complete randomized design (CRD). The characteristics of the experimental test are 4 times treatment 1 time repetition in a homogeneous sample population. The conclusion of the research is that the provision of artificial eco enzyme has an effect in the form of an average increase and decrease in each parameter of the water quality of the dug well, namely pH 0,4, TDS 22 mg/l, TSS 13,3 mg/l, DO 4,2 mg/l, NH3 2,5 mg/l, Fe 0,4 mg/l, and Mn 0,03 mg/l. Based on one-way ANOVA testing resulted in sig. 0.001 0.05 and Duncan testing resulted in different number notations in each sample with sig. 1.000 0.05 which means the addition of eco enzyme gives a real influence on improving the quality of well water.